Development of virtual reality math media in the junior high school Indonesia-Malaysia with group investigation model - Buchori, Achmad; Osman, Sharifah (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
Conventional mathematics learning is felt to be less interesting and boring for students. Students need innovative learning and make students active in learning. To improve students' understanding of learning mathematics, innovation is needed in innovative learning media. This study aims to produce a product in the form of virtual reality media in mathematics learning based on the group investigation model. This study uses the ADDIE research method with analysis, design, development, implementation, and evaluation stages. Before being tested, the media was validated by a media expert validator with a result of 86% in the "Very Good" category and a material expert with an assessment result of 94% in the "Very Good" category so that "VR Math" was declared valid. The results of the VR Math learning media trial showed that (1) the results of calculating the percentage of students' learning completeness in the experimental class were 90%, (2) the average learning outcomes of the experimental class were better than the control class, (3) there was an increase indicated by a score of N -0.76 gain in the “High” category. Based on the results of the trial, the VR Math learning media was effective for group investigation-based mathematics learning based on the effectiveness indicator, namely achieving 90% classical learning mastery, the experimental class learning outcomes were better than the control class, and there was an increase